Non-isothermal Evaporation of Salt Solutions on a Microstructured Surface; Nanoscale and Microscale Thermophysical Engineering; Vol. 18, iss. 3 - Misyura S. Ya. Sergey Yakovlevich (2018, 2018)
Title screen